ANALYSIS OF THE EFFECT OF FOREIGN DIRECT INVESTMENT, GOVERNMENT SPENDING, AND EXPORTS ON ECONOMIC GROWTH ASEAN-5 COUNTRIES, 2005-2017 - Ali Zainal Abidin (Journal of Applied Economics in Developing Countries, 2021)
Foreign investment, exports, and government spending are some of the variables closely related to a country's development. This study aims to look at the relationship between foreign direct investment (FDI), export values, and government spending on economic growth in ASEAN-5 countries. These countries include Indonesia, Malaysia, the Philippines, Vietnam, and Singapore. The research method uses a quantitative approach with panel data analysis. The type of data is secondary data from the World Bank database from 2005 to 2017. The data is then tested through the Breusch and Pagan tests and the Hausman test. Finally, the data were analyzed using panel data regression analysis. The study result shows that FDI and exports have a positive but not significant effect on economic growth in ASEAN-5 countries. Meanwhile, the government expenditure variable has a positive and significant influence on the economic growth of ASEAN-5 countries. These results can also be used as a basis for policymakers on the volume of economic growth, especially in encouraging the quality of human resources to boost export value in ASEAN-5 countries.Keywords: ASEAN-5; Economic growth; Exports; FDI; Government spending